Metalúrgica Longra (1920-1993) : ancoragem para um estudo sob os regimes de acção - Lage, M. Otília P. (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Built upon two levels – the factual and the critically referential –, this history of Longra Steelworks (Metalúrgica da Longra – M.L.): workshop, factory, company – congregates a diversified plurality of discourses united in empirical and theoretical research, a documentary corpus necessary for the factory’s structural approach. Appearing in 1920, in a rural space (Felgueiras), in 1970 is one of Portugal’s leading companies in the office furniture and industrial furniture design sector.